Training report: RDP phase II 1990-1992 - BRAC (© BRAC, 2016)
1. Io RDP phase II, training played a vital role by disseminating information, channeling appropriate skills, helping to possess tailored attitudes, and developing professionals in development management for addressing the clientele needs. 2. A total of 491,241 participants were trained in RDP Phase-II, during 1990- 1992. Of them 96.63, 0.91, 0.51, and 1.94percent were group members, NFPE teachers, gram sbeboks, and BRAC staff respectively. Among the group members, 84.60 percent went for employment and income generation activities and 12.04 percent for human development training. This was hopefully contributed RDP to acltieve its objectives i.e.; poverty alleviation and empowerment of the poor people. 3. The overall target for training during this phase was 403,444 but actually 491,241 was covered. It means the coverage exceeded the actual target by 21.8 percent. The coverage of participant by category was; 474,718 (120.5%) group members, 4,456 (98.9%) NFPE teachers, 2,520 (369.5%) gram slteboks, and 9,457 (219.7%) BRAC staff. During this phase, 76 types of courses were conducted as against 60 planned. These variations were made to address the emergent needs of the program. 4. Structured operations related courses such as 'Operations Management Course', 'Village Organisation and Credit Management' etc. were found to be worthwhile for better program implementation. With this ends, job related training curr iculum will be developed in RDP phase m. 5. Trainers/Faculty Members should have uptodate program experience to cope with the courses. The endeavour